92. Characteristics and Outcomes of Deep Brain Stimulation Device Related Infections: Experience from Quaternary Centers. (4th December 2021) - Tabaja, Hussam; Tai, Don Bambino Geno; Corsini Campioli, Cristina G; Chesdachai, Supavit; DeSimone, Daniel; Mahmood, Maryam
Abstract: Background: Increasing use of deep brain stimulation (DBS) over the past 20 years is paralleled by a rise in DBS infections. There is a paucity of data on the diagnosis, management, and outcomes in such infections. We describe our center's experience with DBS infections. Methods: Adults ( >18 years) diagnosed with DBS associated infection between January 1, 2000 and May 1, 2020 were retrospectively reviewed. Data on patient demographics, clinical presentation, microbiology, and management was collected. Results: Seventy cases were identified (table 1 ). The mean age at diagnosis was 58.9 ± 16.5 years. The bulk were free of comorbidities. Parkinson's disease and essential tremors were the most common indications for DBS placement. The median time from implantation to infection was 4 months [IQR 1, 24]. The neurotransmitter and extension wires were the most frequently infected parts. A microbiological diagnosis was made in 89% of cases, 47% of which were polymicrobial. The most commonly identified organisms were Staphylococcus aureus, Cutibacterium acnes, and coagulase-negative staphylococci . For patients with deep infection, 71% had complete device extraction, 20% partial extraction, and 9% device retention; clinical cure at 3 months occurred in 97%, 64% and 100%, respectively (figure 1 ). On the other hand, 93% of patients with superficial infection had device retention; cure at 3 months was seen in 64% (figure 2 ). Suppressive oral antibiotics were rarely used, 45% of patients with partial extraction and 26% with device retention. DBS was reimplanted in 71% of patients after complete extraction and led to reinfection in 30% at 1 year follow up. Median time to reimplantation was 2.7 months. All patients who failed at 3 months in the partial extraction and device retention cohorts subsequently underwent complete device removal leading to clinical cure sustained at 1 year follow up. Conclusion: All patients who had complete extraction achieved clinical cure at 3-months follow-up, while high failure rates occurred in those with device retention. Most infections were polymicrobial and predominantly caused by gram-positive pathogens. Thirty percent of patients with re-implantation after complete device extraction developed re-infection within 1 year. Disclosures: All Authors : No reported disclosures